1997
DOI: 10.1001/archpsyc.1997.01830190088009
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Synaptophysin Immunoreactivity in the Prefrontal Cortex of Subjects With Schizophrenia

Abstract: Additional studies are required to determine if the decrease in levels of synaptophysin immunoreactivity is caused by a decrease in the number or size of presynaptic terminals, a decrease in the number of synaptic vesicle per terminal, or a decrease in the expression of synaptophysin. However, all of these potential explanations are consistent with a disturbance in synaptic transmission in the prefrontal cortex of patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(58 citation statements)
references
References 0 publications
7
50
0
1
Order By: Relevance
“…Inappropriate dendritic arborization, spinogenesis, and synaptic connections lead to inappropriate connectivity and altered excitation-inhibition balance (McGlashan and Hoffman, 2000; Spronsen and Hoogenraad, 2010; Duman and Aghajanian, 2012). This is supported by observations of decreased dendritic spines and synaptic labeling in post mortem cortex of schizophrenic patients (Glantz and Lewis, 1997, 2000; Honer et al, 1999). Thus, synaptogenesis can be altered by any of the previously discussed developmental events and plays an important role in neuropsychiatric disease pathology.…”
Section: Developmental Effects Of Dopaminergic Modulationsupporting
confidence: 68%
“…Inappropriate dendritic arborization, spinogenesis, and synaptic connections lead to inappropriate connectivity and altered excitation-inhibition balance (McGlashan and Hoffman, 2000; Spronsen and Hoogenraad, 2010; Duman and Aghajanian, 2012). This is supported by observations of decreased dendritic spines and synaptic labeling in post mortem cortex of schizophrenic patients (Glantz and Lewis, 1997, 2000; Honer et al, 1999). Thus, synaptogenesis can be altered by any of the previously discussed developmental events and plays an important role in neuropsychiatric disease pathology.…”
Section: Developmental Effects Of Dopaminergic Modulationsupporting
confidence: 68%
“…As a result, the synaptic architecture of the PFC may remain in an excessively plastic, permanently juvenile state where synapses and thus functional cortical circuits fail to be stabilized, compromising the integrity, stability and fidelity of PFC circuits that are necessary for reliable and predictable information processing and may thereby contribute to the onset of schizophrenia and the persistent symptomatic and cognitive deficits that characterize the course of this chronic debilitating illness. This scenario may, at least in part, explain the previous postmortem findings of decreased dendritic spines and neuropil in subjects with schizophrenia (48, 62, 63). Consistent with this hypothesis, using a novel free-water imaging technique, it has recently been shown that the extracellular space in the cerebral cortex, of which PNNs are a component, was significantly decreased in first-episode schizophrenia patients (64).…”
Section: Discussionmentioning
confidence: 82%
“…Synaptic structural and ultrastructural changes, altered expression of presynaptic proteins, reduction of dendritic spine density, fewer synaptic vesicles and shrinkage of axon boutons have been reported in several brain regions (Eastwood and Harrison, 1995, Perrone Bizzozero et al, 1996, Uranova et al, 1996, Glantz and Lewis, 1997, Garey et al, 1998, Harrison, 1999, Glantz and Lewis, 2000, Mirnics et al, 2000, Rosoklija et al, 2000, Prabakaran et al, 2004, Clark et al, 2006, Camargo et al, 2007, Le-Niculescu et al, 2007, Sweet et al, 2007, Pennington et al, 2008, Smalla et al, 2008, Sweet et al, 2009, Chan et al, 2010, Chu and Liu, 2010, English et al, 2011). Importantly, synaptic abnormalities have been detected in the entorhinal and perirhinal cortices, regions where CSPG changes were also found (Eastwood and Harrison, 1995, Arnold, 1997, Harrison, 1999, Hemby et al, 2002, Law et al, 2004, Beneyto et al, 2007, Pantazopoulos et al, 2010).…”
Section: Ecm Functions Bear Direct Relevance To the Pathophysiologmentioning
confidence: 98%